2016
DOI: 10.1007/s10862-016-9574-6
|View full text |Cite
|
Sign up to set email alerts
|

Reversal Learning Deficits in Criminal Offenders: Effects of Psychopathy, Substance use, and Childhood Maltreatment History

Abstract: Deficits in reinforcement learning are presumed to underlie the impulsive and incorrigible behavior exhibited by psychopathic criminals. However, previous studies documenting reversal learning impairments in psychopathic individuals have not investigated this relationship across a continuous range of psychopathy severity, nor have they examined how reversal learning impairments relate to different psychopathic traits, such as the interpersonal-affective and lifestyle-antisocial dimensions. Furthermore, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…From a clinical perspective, this finding parallels the commonly seen inclination to keep exhibiting antisocial behaviour despite having faced criminal sanctions (Kiehl & Hoffman, 2011). More recent work, however, has pointed out that reversal learning deficits are found not only in offenders with high psychopathy scores but also in offenders with a subthreshold score on the Psychopathy Checklist-Revised (PCL-R; Hare, 2003) (Dargis, Wolf, & Koenigs, 2017;Mitchell et al, 2006) and in offenders with a diagnosis of antisocial personality disorder without high psychopathy checklist scores (De Brito, Viding, Kumari, Blackwood, & Hodgins, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical perspective, this finding parallels the commonly seen inclination to keep exhibiting antisocial behaviour despite having faced criminal sanctions (Kiehl & Hoffman, 2011). More recent work, however, has pointed out that reversal learning deficits are found not only in offenders with high psychopathy scores but also in offenders with a subthreshold score on the Psychopathy Checklist-Revised (PCL-R; Hare, 2003) (Dargis, Wolf, & Koenigs, 2017;Mitchell et al, 2006) and in offenders with a diagnosis of antisocial personality disorder without high psychopathy checklist scores (De Brito, Viding, Kumari, Blackwood, & Hodgins, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A two-factor approach appears most common in research on psychopathic traits and EFs in incarcerated offenders. Several studies have found support for impulsive-antisocial traits being related to reduced EFs, while interpersonal-affective traits have been related to normal or even superior EFs ( 28 , 43 45 ), although results continue to be inconclusive ( 46 , 47 ). In the few studies that have investigated EFs in relation to the PCL-R four-facet structure, one found a positive association between working memory and interpersonal facet scores ( 26 ), and one has suggested the antisocial facet as related to poor response inhibition, while the affective facet has been related to better response inhibition ( 48 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results raise the possibility of using learning estimates (e.g., v) to detect differences in this population. Moreover, reversal-learning tasks have been used to investigate PTs given their sensitive properties to identify individual differences (Budhani et al, 2006;Gillan et al, 2016;Dargis et al, 2017). Using a multivariable linear regression model, we showed how behavioral differences on the reversal-learning task contained information about the PTs from the HiTOP specters.…”
Section: Discussionmentioning
confidence: 98%